Biventricular Outflow Tract Obstruction After a Rastelli Repair. (May 2016) - Musuku, Sridhar Reddy; Devejian, Neil; Pani, Saroj; Kassel, Kareem
Abstract : Supplemental Digital Content is available in the text.